Implicit and explicit corrective feedback and feedback exposure conditions. Issue 1 (1st April 2020) - Iizuka, Takehiro; Nakatsukasa, Kimi
Abstract : This exploratory study examined the impact of implicit and explicit oral corrective feedback (CF) on the development of implicit and explicit knowledge of Japanese locative particles (activity de, movement ni and location ni) for those who directly received CF and those who observed CF in the classroom. Thirty-six college students in a beginning Japanese language course received either recast (implicit), metalinguistic (explicit) or no feedback during an information-gap picture description activity, and completed a timed picture description test (implicit knowledge) and an untimed grammaticality judgement test (explicit knowledge) in a pre-test, immediate post-test and delayed post-test. The results showed that overall there was no significant difference between CF types, and that CF benefited direct and indirect recipients similarly. Potential factors that might influence the effectiveness of CF, such as instructional settings, complexity of target structures and pedagogy styles, are discussed.